Reiterating the Importance of Publicly Funded and Provided Primary Healthcare for Non-communicable Diseases: The Case of India; Comment on "Universal Health Coverage for Non-communicable Diseases and Health Equity: Lessons From Australian Primary Healthcare" - Sulakshana Nandi (Kerman University of Medical Sciences, 2022)
India has established health and wellness centres (HWCs) and appointed mid-level healthcare providers (community health officers, CHOs) to provide free and comprehensive primary healthcare (PHC), through screening, prevention, control, management and treatment for non-communicable diseases (NCDs), in addition to existing services for communicable diseases, and reproductive and child health. The range of services being provided and the number of people accessing ambulatory care in these government centres have increased, leading to more equitable healthcare access and financial protection. In policy debates, contestations exist prioritising between PHC or hospital services, and between publicly-provided healthcare or privatised and "purchased" services. Nationally and globally the influence of industries and corporations in health governance has weakened the response against NCDs. PHC initiatives for NCDs must be publicly funded and provided, located within communities, and necessitate action on the determinants of health. The experiences from Australia (a high-income country) and India (a low-and middle-income country) amply illustrate this.